¿Mujer/divinidad?: ‘Lo femenino’ en la iconografía ibérica de época helenística - Tortosa Rocamora, Trinidad (Complutum, 2007)
Goddess - women? Under this binomial swings the traditional interpretation of feminine iconography of Iberic pottery, especially in south-east Spain: Murcia and Alicante. In this paper we present some of the few examples we have conserved and emphasize the presence of “feminine” that becomes a category whose semantic sense traditionally has been linked to aspects of feminine psychology.